Menggagas Paradigma Pertimbangan Hukum Transitif : Ikhtiar Mempertahankan Keluhuran Martabat Hakim Melalui Putusan - Andi Hakim Lubis (Judex Laguens, 2024)
The public places great expectations on the shoulders of judges and our judicial system. Because one of the essential instruments in law enforcement for justice seekers can be obtained through judges' decisions, a judge's decision in an epistemological perspective is a struggle of a judge's thoughts, both with his heart and conscience, logic, and other judges in his environment. The judge's decision has the power to transfer ownership, revoke freedom, limit arbitrariness, and even more fundamentally eliminate a person's right to life. Such a fundamental authority should be exercised in the right way, considering that the responsibility is not only horizontal but also vertical. However, the fact is that recently, there has been a dichotomy; not a few judges' decisions have triggered the birth of criticism and cynicism, equivalent to public distrust, and formed an attitude of doubt towards judges. This is saddening because not a few judges have mortgaged their dignity and nobility, resulting in decisions that do not reflect universal safety. Observing some of the urgency of judges' decisions in our judicial system, a new legal paradigm is needed, which becomes a grand design in carrying out the duties and decision-making of judges, which researchers term transitive. The transitive legal paradigm will be a milestone of justice in maintaining and defending the dignity of judges as representatives of God. Transitive means saving, reconciling, prospering, and making happy. The judge's decision ultimately becomes a universal salvation that is represented as a representative of God by prioritizing legal considerations for the common good. Thus, the transitive legal paradigm in judges' decisions will provide benefits for all parties, including judges, and the development of the law in the future. Keywords: Paradigm, Law, Consideration, Transitive, Judge